Inventoras de trilhas: História e Memórias das professoras das escolas rurais do município de Uberlândia-MG (1950 a 1980) - Assis, Danielle Angélica de (2018)
This study seeks to understand how rural school teachers of Uberlândia, state of Minas Gerais, organized their practices before and after the 5692/71 Law by analyzing their history and their memories between 1950-1980. This study was conducted within the field of History of Education, from the perspective of Cultural History. The period selected was divided in two important historical moments: the first one is the period between 1950 and 1960, when rural education was predominantly provided by lay teachers; the second is the period after the 5692/71 Law, which required that teachers who worked at primary school (up to 4th grade) must have a minimum level of education (High School). The selection goes until 1980, when the process of nucleation of rural schools begins in the city and several transformations happen in these institutions' organization. The proposed aims were: to analyse the pedagogical practices adopted by the rural school teachers; to understand the relationship between training and teaching practices; to get to know these professionals working conditions; to perceive the representations these teachers built by themselves about their occupation and to perceive the meanings they attributed to their career. To achieve these goals, I made use of written and spoken sources. The written sources analyzed were notebooks of tests and activities, teaching planning notebooks, notes, short messages, attendance records, enrollment records, rural school passing records, school meetings minutes, legislative minutes, newspapers, the municipal education report and the municipal education plan. The spoken sources analysed were interviews with six teachers who have worked in rural schools. For the analysis of the documentation I used the following categories: teacher training, pedagogical practices, working conditions and representations. I found that the inventiveness of the empirical culture was underlying the practices implemented by the teachers. I also noticed the existence of conflicts between rural education, public authorities and local elites. The changes brought about by the 5692/71 Law, which culminated in buildings' improvements and in the provision of training courses for the teachers, were also noticed. Thenceforth, I concluded that the knowledge acquired through the teacher training courses was not very applicable in the classrooms because they were disconnected with the needs and the reality of rural areas, even though they systematized the rural education curriculum and introduced the teaching program in an apostille form. I realized that the lay teachers gained their knowledge through practice and therewith they constructed their own ways of walking. They used their inventiveness, solidarity and resistance to create their own ways of making things. These ways followed on the literacy of rural populations and, by training themselves through practice, these professionals became "poets of their business", "inventors of pathways".